Pengembangan Media E-Modul Dalam Meningkatkan Minat Siswa Dalam Pembelajaran Ekosistem di SD/MI - N, Nurhafizah; Azhari, Yunita; Syafitri, Nadia; Tanjung, Riska Rahman; Sari, Putri Puspita (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to explain the results and process of developing e-module learning media for ecosystem materials. Researchers developed e-module media on ecosystem material using the ADDIE research model and only reached the Analyze, Design and Development stages. The data collection technique used was a validation questionnaire to assess the feasibility of the e-module. The validation results from media experts obtained a score of 95%, meaning that the e-module was categorized as very suitable for use. Meanwhile, the validation results from material experts obtained a score of 90%, which means that the e-module is very suitable for use to increase students' interest in ecosystem learning.